Clinical factors associated with shorter durable response, and patterns of acquired resistance to first-line pembrolizumab monotherapy in PD-L1-positive non-small-cell lung cancer patients: a retrospective multicenter study - Kazutaka Hosoya; Daichi Fujimoto; Takeshi Morimoto; Toru Kumagai; Akihiro Tamiya; Yoshihiko Taniguchi; Toshihide Yokoyama; Tadashi Ishida; Hirotaka Matsumoto; Katsuya Hirano; Ryota Kominami; Keisuke Tomii; et al. (BMC Cancer, 2021)
Abstract Background Despite the wide-spread use of immune checkpoint inhibitors (ICIs) in cancer chemotherapy, reports on patients developing acquired resistance (AR) to ICI therapy are scarce. Therefore, we first investigated the characteristics associated with shorter durable responses of ICI treatment and revealed the clinical patterns of AR and prognosis of the patients involved. Methods We conducted a retrospective multi-center cohort study that included NSCLC patients with PD-L1 tumor proportion scores of ≥50% who received first-line pembrolizumab and showed response to the therapy. Among patients showing response, progression-free survival (PFS) was investigated based on different clinically relevant factors. AR was defined as disease progression after partial or complete response based on Response Evaluation Criteria in Solid Tumors. Among patients with AR, patterns of AR and post-progression survival (PPS) were investigated. Oligoprogression was defined as disease progression in up to 5 individual progressive lesions. Results Among 174 patients who received first-line pembrolizumab, 88 showed response and were included in the study. Among these patients, 46 (52%) developed AR. Patients with old age, poor performance status (PS), at least 3 metastatic organs, or bone metastasis showed significantly shorter PFS. Among 46 patients with AR, 32 (70%) developed AR as oligoprogression and showed significantly longer PPS than those with non-oligoprogressive AR. Conclusions Patients with old age, poor PS, at least 3 metastatic organs, or bone metastasis showed shorter durable responses to pembrolizumab monotherapy. Oligoprogressive AR was relatively common and associated with better prognosis. Further research is required to develop optimal approaches for the treatment of these patients.